Empowering Student Behavioral Engagement in Thai EFL Writing Classes through a Multimodal Project Approach: Insight from Students' Perspectives - Azalia, Ataillah Calista; Srikandi, Cut Novita (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to investigate how a multimodal project approach empowers student behavioral engagement in Thai EFL writing classes, based on learners’ perspectives. The research is grounded in the genre-based multimodal framework and guided by student engagement, focusing on peer interaction, teacher interaction, and content engagement. Using a quasi-experimental mixed-method design, 30 tenth-grade students at Islam Suksa Darulbir Satun School, Thailand, participated in a classroom action research intervention. Data collection involved surveys, classroom observations, multimodal writing products, and reflective responses. The intervention followed four stages: understanding multimodality, designing, revising drafts, and publishing with reflection. Results showed statistically significant increases in engagement across all domains (p 0.001). Students demonstrated improved collaboration, responsiveness, and focus. Reflections highlighted greater confidence and enjoyment, especially when writing tasks connected with daily experiences and allowed creative visual expression. The study concludes that multimodal writing projects effectively enhance behavioral engagement by aligning learning with students’ digital strengths and fostering autonomy. These insights offer practical direction for improving EFL writing instruction in similar educational contexts.